STUDIES ON FIRE RETARDANT MILITARY UNIFORMS - Saket Totala,; Siddhant Dinesh Katariya ,; Anurag Rajendra Jhanwar, (International Journal of Innovations in Engineering Research and Technology, 2021)
Military sector is one of the most textile demanding sector with various special and critical requirements. Application of Nonwovens in the field of Flame Retardancy (FR) Uniforms will not only be cost effective but also can be produced at higher production speeds compared to conventional woven technology. In battlefield solider are exposed to flame threats and thermal radiative, thus it gives need to the use of FR Uniformsin the Military Sector. The following paper discusses the current commercially available FR Military Uniforms and material which it is made of, fibers available for forming FR Military Uniforms and Special FR Finishes for Fire Retardancy of the fabric